Using Patient Focus Groups to Respond to Patient Satisfaction Surveys. - Schrag, LMSW, ACSW, Wendy Funk (The Journal of Nephrology Social Work, 2006)
Using Patient Focus Groups to Respond to Patient Satisfaction Surveys.